PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DAN PEGAWAI PADA SDN KEBONSARI KULON I - Nivan Triyo Irawan Suwarno; Tumini Tumini; Elok Dwi Vidiyastutik (Universitas Panca Marga, 2024)
This research was conducted at SDN Kebonsari Kulon I with the aim of examining the influence of leadership, motivation and work discipline on the performance of teachers and employees at SDN Kebonsari Kulon I. Quantitative research with causal associative relationships is the type of research used. The population in this study was 32 teachers and employees. The sample used in this research was non-probability sampling with a saturated sampling technique, totaling 32 people. The results of this research show that: (1) leadership influences the performance of teachers and employees (2) motivation influences the performance of teachers and employees (3) work discipline influences the performance of teachers and employees.